2011
DOI: 10.1099/jmm.0.027409-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia and breast abscess: unusual extra-intestinal manifestations of Clostridium difficile infection

Abstract: Extra-intestinal manifestations of Clostridium difficile infection are uncommon. Most cases are associated with gastrointestinal disease and often occur as a mixed infection with other gut flora. We report a case of breast abscess following monomicrobial C. difficile bacteraemia in a female with background chronic hepatitis C infection and alcoholic liver disease. No evidence of colitis was found. Our case shows that C. difficile is indeed capable of spreading from the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Clostridium difficile always causes antimicrobialassociated diarrhea. Extracolonic C. difficile infection is rare, and the manifestations include osteomyelitis (3), visceral abscess, reactive arthritis (4), and breast abscess (5). Clostridium difficile bacteremia is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clostridium difficile always causes antimicrobialassociated diarrhea. Extracolonic C. difficile infection is rare, and the manifestations include osteomyelitis (3), visceral abscess, reactive arthritis (4), and breast abscess (5). Clostridium difficile bacteremia is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…For the two strains, from blood and stool, the same toxin profile was observed, ST type and antibiotic susceptibility pattern. The cases of Clostridium bacteremia similar to the current one were reviewed in the PubMed database and listed in Table 1 (5,9,10) and Table 2 (10-14) for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gérard et al characterized a serogroup C strain and McGill et al reported two ribotype 106 strains and one ribotype 001 [36], [47]. Another case report detected a ribotype 106 from bacteremia and breast abscess [48]. One of two bacteremia cases recently reported by Hemminger et al was due to the epidemic and hypervirulent NAP1 strain (027/BI, toxinotype III, binary toxin-positive), and the other was due to NAP-4 [49].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Extra-intestinal manifestation of C. difficile had been reported in the form of bacteremia (Feldman et al 1995;García-Lechuz et al 2001;Jacobs et al 2001;Libby and Bearman 2009;Choi et al 2013;Shah et al 2017), abscesses (Durojaiye et al 2011;Ulger Toprak et al 2016;Roy et al 2017), and rarely had also been associated with osteomyelitis (Riley and Karthigasu 1982;Towns et al 1984;Incavo et al 1988;Pron et al 1995;Gaglani et al 1996;García-Lechuz et al 2001;Bachmeyer et al 2008;Al-Najjar et al 2013;Curtis and Lipp 2013;Ranganath and Midturi 2013). Two previous cases of C. difficile chronic osteomyelitis were reported among sickle cell patients (Gaglani et al 1996;Bachmeyer et al 2008).…”
mentioning
confidence: 99%